2008
DOI: 10.1074/jbc.m806158200
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Membrane-bound Reactants and Products during the Activation of Human Prothrombin by Prothrombinase

Abstract: Membrane binding by prothrombin, mediated by its N-terminal fragment 1 (F1) domain, plays an essential role in its proteolytic activation by prothrombinase. Thrombin is produced in two cleavage reactions. One at Arg 320 yields the proteinase meizothrombin that retains membrane binding properties. The second, at Arg 271 , yields thrombin and severs covalent linkage with the N-terminal fragment 1.2 (F12) region. Covalent linkage with the membrane binding domain is also lost when prethrombin 2 (P2) and F12 are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
(59 reference statements)
3
25
0
Order By: Relevance
“…Isothermal titration calorimetry of F12 binding to IIa TAT yielded heat traces and an isotherm (Fig. 1) intermediate to those expected from previous measurements of F12 binding to P2 or thrombin (18). Thus, the thermodynamic constants for F12 binding are apparently sensitive to subtle aspects of proteinase formation beyond simply reporting on the cleavage, or lack thereof, at the Arg 15 -Ile 16 bond.…”
Section: Distinguishing Zymogen-like and Proteinase States Ofmentioning
confidence: 62%
See 3 more Smart Citations
“…Isothermal titration calorimetry of F12 binding to IIa TAT yielded heat traces and an isotherm (Fig. 1) intermediate to those expected from previous measurements of F12 binding to P2 or thrombin (18). Thus, the thermodynamic constants for F12 binding are apparently sensitive to subtle aspects of proteinase formation beyond simply reporting on the cleavage, or lack thereof, at the Arg 15 -Ile 16 bond.…”
Section: Distinguishing Zymogen-like and Proteinase States Ofmentioning
confidence: 62%
“…The large thermodynamic differences in the binding of F12 to zymogen relative to proteinase are surprisingly not observed with fragment 2 produced by proteolysis of F12 (18). Studies with EDTA did not reduce F12 binding to that observed with fragment 2 (data not shown).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Researchers have used synthetic lipids (16,20), as well as lipids derived from natural sources (21,22). In our work, we use synthetic lipids because they are chemically more stable.…”
Section: Resultsmentioning
confidence: 99%